Gendered Voices and the Public Sphere: Epistolary Discourse in Eighteenth-Century British Literature - Jogthong, Chalermkwan; Intachai, Sunisa; Phuttichart, Prapit (Journal for Developing the Social and Community, 2025)
Background and Aims: This study fills a gap in existing scholarship by applying Jürgen Habermas’s public sphere theory to gendered literary discourse in eighteenth-century Britain. Specifically, it examines how gendered communication in letter-writing and satire contributed to shaping early modern ideas of the public sphere. Methodology: Using a qualitative literary approach that incorporates textual analysis and comparative reading, the research investigates Samuel Richardson’s Pamela; or Virtue Rewarded (1740) and Tobias Smollett’s The Expedition of Humphry Clinker (1771). Results: The analysis reveals how these works negotiate the complex boundaries between private domestic life and public political discussion. The findings highlight a distinct contrast between the texts: Pamela demonstrates women’s indirect participation in public life through private letter-writing, effectively transforming domestic confinement into public influence. Conversely, Humphry Clinker offers a broader satire of social and political transformation, reflecting anxieties regarding class mobility and the changing structure of British society. Ultimately, the study challenges the limitations of Habermas’s framework regarding women’s participation, proposing that these eighteenth-century novels served as active spaces for public dialogue and moral debate. Conclusion: This research underscores the significant role of literary form in reflecting and influencing the development of public sphere concepts during this period.